O ensino de Química e o desenvolvimento da aprendizagem a partir da relação entre as TICs e a experimentação em sala de aula - Silva, Vitor de Almeida (2016)
This research describes the relevancy of internet information access to development learning in chemistry teaching, departing from two features: theoretical aspect and experimentation. The study was conducted in a class of 1st year of high school at a public school in the metropolitan area of Goiânia. The students were organized into groups and then chose a subject they had interest in being investigated. Thereunto, the students used the Information Comunication Tecnologies (ICT) as main access to information about the subject they had chosen. The information accessed was from any site available on the internet. The research object was characterized by the student’s social interaction, comprehension and manipulation of the information and experimental activity development in classroom which approached chemistry knowledge through the use of internet. Thus, this study was built up in four steps: 1º) the choice of the subject by students; 2º) the virtual bibliographic survey; 3º) the questionnaire and discussion of the topic; 4º) the experimentation and the communication about the subject chosen. We used collaboration-cooperation theory to understand how the students handled the information to solve questions as well as to verify how the development of the cognition could be improved with the use and discussion of information accessed on the internet. The result shows that students use the information as a product that could be fragmented and later copied without establishing any comprehension about it. This demonstrated that students’ behavior considered the copy as a means to understand the information content. That happens when the sign present in information is misunderstood, consequently the student organizes his/her cognitive representation through the copy. This represents a low level of Piaget’s Equilibrium. In relation to teamwork they assume the collaboration state, that is, the intention of the group is to solve the questionnaire together. However, this doesn’t happen and the group distributes one question for each member to solve it. This is a way to work cooperatively. This means that the working group is fragmented not only physically, but cognitively. There are those who perform the activity and others who criticize what is done. We observe that in the moment of discussion about the subject chosen by the students, there is an improvement of knowledge of them. In this process, the teacher’s role is understood as a mediator, driving the students to comprehend the information beyond the common sense and previous knowledge. The work in laboratory showed to students the importance of chemistry knowledge to plan, execute, comprehend and formulate an intelligent explanation about the phenomenon investigated. It is present the streamline study of the sign that wasn’t comprehended by students and this enabled the teacher to develop the students from low to more complex levels regarding the Piaget’s equilibration processes. We concluded that the learning development, related to ICTs and experimentation classroom, is able to promote the development of an epistemological curiosity making it possible a scientific learning and a critic formation of the citizens.